Rousseau: Da Propriedade Privada À Alienação - Ferreira, Fernando Henrique [UNIFESP] (2017)
This research aims to detect the possible joints that can be establish between the concept of private property and the degeneration of the human essence in the work of Jean-Jacques Rousseau. As a conductor of the discussions, it’s taken the concept of private property as is exposed in Discours sur l’inégalité. The analysis will try to demonstrate the possible relationships between the notion of “alienation” and private property; furthermore, it will demonstrate that the lands appropriation held through work is in the genesis of the man’s removal from his natural essence. To elucidate the relationships proposed by the author between man alienation and moral corruption, it is intended not only to understand the moral and political aspects of Rousseau’s thought, but also the problems related to the advent of private property.